1994
DOI: 10.1111/j.2044-8341.1994.tb01800.x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between ward atmosphere and staff attitude to treatment in psychiatric in‐patient units

Abstract: The relationship between staff ratings of ward atmosphere, their attitude to treatment, and their direction of interest was investigated in four psychiatric in-patient units. Two general admission units, one intensive care unit, and one regional secure unit were studied. Fifty-eight psychiatric nurses rated their units using the Ward Atmosphere Scale-Form R (WAS) and expressed their direction of interest and attitude to treatment on the Direction of Interest Questionnaire and the Attitude to Treatment Question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 8 publications
1
13
0
Order By: Relevance
“…Alden (1978) found that eight of the ten subscales formed one factor while the other two formed one factor each. Squier (1994) also found a three factor solution but with two of the factors consisting of four subscales each. Rossberg and Friis (2003) pointed out that due to the changes in psychiatric settings the phraseology in the WAS appeared to be outdated for some items (e.g., "One may interrupt the doctor").…”
Section: Criticism Of the Measurement Toolsmentioning
confidence: 88%
“…Alden (1978) found that eight of the ten subscales formed one factor while the other two formed one factor each. Squier (1994) also found a three factor solution but with two of the factors consisting of four subscales each. Rossberg and Friis (2003) pointed out that due to the changes in psychiatric settings the phraseology in the WAS appeared to be outdated for some items (e.g., "One may interrupt the doctor").…”
Section: Criticism Of the Measurement Toolsmentioning
confidence: 88%
“…Second, it was also of interest to investigate the staff perception of social climate. This was thought relevant as staff attitudes to treatment have been reported to affect the social climate of psychiatric units (Squier, 1994), and although no known studies have reported a link between the social climate of secure units and staff occupational stress (Kirby & Pollock, 1995), social climate has been linked to violence within psychiatric units (Friis & Helldin, 1994) as well as staff morale (Moos & Schaefer, 1987). Given the findings of previous research and the client type catered for by the secure facility, it was hypothesized that (a) adolescents would rate the social climate of the facility in a more negative direction than staff and (b) adolescents and staff would rate the social climate of the open units in a more positive direction than the social climate of the secure units.…”
mentioning
confidence: 99%
“…It is also important to note some of the correlations between attitude scales such as the ATQ and certain demo-graphic variables such as education and age. Whilst Caine et al (1982) report no correlation between educational achievement and ATQ or DIQ scores, Registered Mental Nurses have been reported as being significantly less biologicallconservative than unqualified nursing staff (Squier 1994). Similarly, medical staff have been reported as being more 'psychological' on the ATQ than Registered Nurses (Caine et af.…”
Section: Questionnaire the Battery Also Includes A Treatment Expectamentioning
confidence: 99%
“…1981). Older nurses tend to be more conservative in their attitudes than their younger colleagues (Proctor & Hafner 1991, Squier 1994).…”
Section: Questionnaire the Battery Also Includes A Treatment Expectamentioning
confidence: 99%
See 1 more Smart Citation